High Anion Gap Metabolic Acidosis as a Result of 5-Oxoproline - Suvika Patel; Falguni Parikh; Niranjan Kulkarni (Indian Journal of Medical Specialities)
High anion gap metabolic acidosis is a common acid–base disorder encountered in hospitalized patients and more so in the intensive care unit. The most common causes are accumulation of lactate, ketones, and urea and ingestion of certain toxins. In the absence of these, lesser-known etiologies such as accumulation of D-lactate or pyroglutamic acid (PGA) should be suspected. PGA (5-oxoproline) is an endogenous organic acid that can accumulate in serum to cause anionic gap metabolic acidosis. This can occur with inherited defects in enzymes that participate in the y-glutamyl cycle or can be acquired in association with therapeutic paracetamol use, malnutrition, sepsis, antibiotics, and renal impairment. Our case illustrates that prompt recognition of this entity and discontinuation of offending agents such as paracetamol result in rapid recovery, thus reducing the hospital stay.